2009
DOI: 10.1038/sj.bjc.6605343
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib monotherapy in patients with relapsed, advanced, or metastatic breast cancer: efficacy, safety, and biomarker results from Japanese patients phase II studies

Abstract: BACKGROUND: HER2-positive metastatic breast cancer (MBC) relapsing after trastuzumab-based therapy may require continued HER2 receptor inhibition to control the disease and preserve the patients' quality-of-life. Efficacy and safety of lapatinib monotherapy was evaluated in Japanese breast cancer patients after trastuzumab-based therapies. METHODS: In studies, EGF100642 and EGF104911 evaluated the efficacy and safety of oral lapatinib given 1500 mg once daily in patients with advanced or MBC. All patients pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 28 publications
3
51
1
Order By: Relevance
“…Further, unlike conventional mucositis, oral lesions secondary to targeted agents are often accompanied by a skin rash. These observations suggest that the pathogenic mechanisms of targeted therapy-induced toxicity are not necessarily the same as for other cancer treatments, and there remains a vast gap in our knowledge regarding the biological mechanisms responsible [81][82][83]. The term "stomatitis" has been used in several recent publications for oral lesions secondary to targeted agents to distinguish them from mucositis secondary to conventional chemotherapy and radiation therapy.…”
Section: Targeted Anti-cancer Agents and Mucosal Injurymentioning
confidence: 99%
“…Further, unlike conventional mucositis, oral lesions secondary to targeted agents are often accompanied by a skin rash. These observations suggest that the pathogenic mechanisms of targeted therapy-induced toxicity are not necessarily the same as for other cancer treatments, and there remains a vast gap in our knowledge regarding the biological mechanisms responsible [81][82][83]. The term "stomatitis" has been used in several recent publications for oral lesions secondary to targeted agents to distinguish them from mucositis secondary to conventional chemotherapy and radiation therapy.…”
Section: Targeted Anti-cancer Agents and Mucosal Injurymentioning
confidence: 99%
“…The PIK3CA activating mutations (E545K and H1047R) cause resistance to lapatinib 58 . Patients with tumors harboring an H1047R PIK3CA mutation or low expression of PTEN, derived clinical benefit from lapatinib in one phase II study 92 .…”
Section: Pik3camentioning
confidence: 99%
“…Knockdown of PTEN did not alter response to lapatinib in vitro and PTEN loss was not associated with reduced response to lapatinib in a phase II monotherapy trial in IBC, as approximately 70% of responders showed PTEN deficiency 9,87,96 . Patients with tumors harboring an H1047R PIK3CA mutation or low expression of PTEN derived clinical benefit from lapatinib in one phase II study 92 . On the other hand, a combined in vitro and in vivo study using a genome wide loss-of-function short hairpin RNA (shRNA) screen identified loss of PTEN expression as one of causes of lapatinib resistance 58 .…”
Section: Ptenmentioning
confidence: 99%
“…This PTEN protein loss was observed in 20.5-76.3% of the HER2-positive breast cancer cases (6)(7)(8)(9)(10), demonstrating an existing correlation between the treatment effect of T and the level of PTEN protein expression (6,7). PIK3CA mutation is observed in 10.3-37.5% of the HER2-positive breast cancer cases (9)(10)(11)(12). Exons 9 (E542K, E545K) and 20 (H1047R) are the hot spots for mutation (13,14), demonstrating that the effect of T treatment was affected by these mutations (10).…”
Section: Introductionmentioning
confidence: 99%
“…Exons 9 (E542K, E545K) and 20 (H1047R) are the hot spots for mutation (13,14), demonstrating that the effect of T treatment was affected by these mutations (10). However, the effect of lapatinib treatment has been proven not to be correlated with the p95HER2 expression levels or PTEN proteins, or the status of PIK3CA gene mutation (8,11,12,15). These biological features are worth examining in terms of their treatment response to T or lapatinib.…”
Section: Introductionmentioning
confidence: 99%